Into the Writers’ Room: Looking at Polish Characters in Contemporary Dutch-Language Audiovisual Fiction Through the Lens of Production Research - Van Heuckelom, Kris (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This article looks into the genesis and development of Poland-related subject matter in foreign audiovisual media. It does so by adding a production-oriented perspective to the scholarly debate surrounding the appearance and instrumentalization of Polish characters in non-Polish TV shows. While pointing to the contingency – rather than the inevitability or the complete arbitrariness – of certain representational practices, this research draws on a series of samples and examples taken from the media landscape that the author is most familiar with, namely, contemporary audiovisual fiction produced in the Dutch language. The article is largely based on a range of semi-structured interviews conducted with Belgian screenwriters who have been closely involved in the creation and development of Polish characters for Flemish TV and film over the past three decades.